Citric acid-assisted phytoextraction of trace elements in composted municipal sludge by garden plants. (1st November 2021) - Leng, Yaling; Lu, Minying; Li, Feili; Yang, Boxuan; Hu, Zhong-Ting
Abstract: Sludge landscaping after compost stabilization is a popular recycling process; however, until trace elements (TEs) are extracted by plants and reduced to safe concentrations, they present a potential exposure risk. Three garden plants, Liriope platyphylla Wang et Tang ( L. platyphylla ), Iris tectorum Maxim ( I. tectorum ), and Photinia x fraseri Dress ( P. x fraseri ), were selected for field experiments, and their ability to phytoremediate TEs and the promotion effect of citric acid (CA) were studied over 3 months of observation. Among the three kinds of plants, L. platyphylla had the highest biomass per unit soil area, and the CA treatment further increased the biomass of this plant per unit soil area as well as the uptake of TEs. When treated with 3 mmol kg −1 CA, L. platyphylla showed increases in the bioconcentration factors of Cu, Zn, Pb, and Cd by 24%, 63%, 27%, and 123%, respectively. Because of the large biomass and high concentrations of TEs, L. platyphylla had high phytoremediation indexes for Zn, Cu, Pb, Ni, and Cd, which reached 18.5, 3.7, 3.2, 2.2, and 0.4 mg m −2, respectively, and were further improved by 60%–187% by the CA treatment. These advantages indicate the potential usefulness of L. platyphylla for phytoremediation. The results provide basic data and technical support for the use of sludge-based compost and phytoremediation by garden plants. Graphical abstract: Image 1 Highlights: The remediation capacity of 3 garden plants to trace elements (TEs) is compared. L. platyphylla has the highest biomass per unit area among the three plants. L. platyphylla shows the high bioconcentration factors towards most trace elements. CA improves the biomass and the bioconcentration factors of L. platyphylla. CA enhances the phytoremediation index of TEs in L. platyphylla by 60%–187%.